Sperm Membrane Stability: In-Depth Analysis from Structural Basis to Functional Regulation - Shan-Hui Xue; Bing-Bing Xu; Xiao-Chun Yan; Jia-Xin Zhang; Rui Su (Veterinary Sciences)
Sperm membrane stability is a key factor in determining sperm viability and fertilization capability, with broad implications ranging from basic reproductive biology to livestock breeding practices. This comprehensive review examines the structural and functional mechanisms underlying sperm membrane integrity, including defensive barrier functions, potentiometric ion channel regulation, and motility modulation that collectively optimize sperm survival, motility, and fertilization potential. Environmental factors such as temperature fluctuations, abnormal pH levels (outside the optimal 7.2–8.2 range), pathological conditions, and hormonal imbalances can compromise membrane stability by inducing oxidative stress and protein denaturation. Key regulatory proteins, notably NPC2 for cholesterol homeostasis, Flotillin proteins for lipid raft organization, and Annexin V for membrane repair mechanisms, demonstrate essential roles in maintaining structural integrity. In livestock reproduction, membrane stability research facilitates the optimization of cryoprotectant formulations and freezing protocols, resulting in 15–25% improvements in post-thaw sperm survival rates and enhanced artificial insemination success. These findings provide valuable insights for advancing assisted reproductive technologies and improving reproductive efficiency in animal husbandry.